Narratives of Scale in the Anthropocene Imagining Human Responsibility in an Age of Scalar Complexity - Dürbeck, Gabriele; Hüpkes, Philip (Taylor & Francis, 2021)
This volume presents an interdisciplinary dialogue between sociology, geography, political sciences, history, and literary, cultural and media studies. Together, they contribute to current debates on the (re-)imagining of forms of human responsibility that meet the challenges created by humanity entering an age of scalar complexity.